INOVASI PEMANFAATAN LIMBAH KULIT BUAH KAKAO SEBAGAI PEWARNA TEKSTIL ALAMI (STUDI KASUS: KAKAO DI KABUPATEN JEMBRANA) - Wulansari, Vita; Utami, Sri; Pramesti, Ni Putu Anggita Okta (Narada : Jurnal Desain dan Seni, 2025)
In the current era, the fashion industry is very developed, high market demand has resulted in mass production of clothing. To prevent the occurrence of fast fashion, world fashion players have now implemented a sustainability system which is done by producing clothes from fabrics made from natural fabric, minimal patterns, and using natural textile dyes. In Indonesia, people now know more about sustainable fashion, one of which is the application of natural textile dyes to fashion products. With abundant natural resources, especially plant species, it can be utilized and has the potential to be developed. One of them is cocoa, cocoa plantations in Indonesia are very developed, especially in Jembrana Regency, Bali, which is the largest cocoa producer in Bali. Cocoa shells are waste that has not been utilized much, in this paper we will present a new innovation in the form of textile dyes from cocoa shell waste, which is expected to help reduce chemical dye pollution in the environment and develop local regional potential in terms of the welfare of local farmers.